Editorial Vol.9(2) - Poudyal, Santosh Raj (The Batuk, 2023)
The holistic growth of people is the main goal of education. The progress of society as a whole is facilitated through education. The Batuk always encourages scholars to engage in research activities to become a balanced human being. This volume (Volume 9, Issue 2), like its predecessor, covers a wide range of activities. The first article in the management section explored the relationship between cyberloafing, workplace rudeness and employee productivity in rural municipalities of ​​Kaski District, Nepal. In addition, another study investigated the quality of management campus services from the perspective of students. Third article examined the credit risk and profitability of commercial banks in Nepal and made comparison between private and joint venture banks. Impact of digital wallet adoption on financial inclusion has been highlighted in the fourth article. Three additional articles with varying scopes are included in the humanities and social sciences part. The focus of the first study of the part is on identifying and analyzing the effects of solar radiation on Pokhara. Another article critically examined the loss and recovery of substance in classical rhetoric. The final article of the issue examined how home, health, emotional, social, and educational factors affect Nepalese bachelor's degree students' college adjustment. We take this opportunity to thank all of the contributors for their outstanding work and unwavering support. The articles that have been published in it are perceptive and thought-provoking, and they offer readers from today's generation useful insights. We are incredibly grateful to the valuable readers of this journal for their invaluable input and helpful suggestions that have helped to make ‘The Batuk’ a lively and dynamic forum for the exchange of ideas.